PENERAPAN METODE KOOPERATIF MODEL THINK PAIR SHARE UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA MATERI OPERASI HITUNG SISWA KELAS 2 SD TERPADU MUHAMMADIYAH I BESUKI SEMESTER I TAHUN PELAJARAN 2012/2013 - Sitti Rosida; Syarif Ibnu Rusydi (Jurnal IKA PGSD (Ikatan Alumni PGSD) UNARS, 2013)
The goal of this research are: 1) To describe the application of methods of cooperative models think pair share to improve learning outcomes math materials arithmetic operations; 2) To improve mathematics learning materials arithmetic operations with the implementation model of cooperative methods think pair share. The method used was action research conducted two cycles. Data collection methods used in this study is the observation, tests, interviews and documentation. This study used a qualitative descriptive analysis techniques. Implementation of this research was conducted in the Integrated SD Muhammadiyah 1 Besuki in class II consisting of 30 students consisting of 16 male students and 14 female students. learning outcomes of students has increased from the first cycle to the second cycle, namely, the first cycle (70%), and the second cycle (86.67%). The conclusion of this study is the model of cooperative methods can think pair share a positive effect on learning outcomes of students of class 2 SDT Muhammadiyah I Besuki, as well as learning methods can be used as an alternative learning Mathematics.